Demographic profile of patients who present for emergency treatment at Wits’ Dental School - Mani, S. P.; Cleaton-Jones, P. E.; Lownie, J. F. (My University, 1997)
The faculties of dentistry and medicine at the University of the Witwatersrand will soon amalgamate into a faculty of health sciences. To help plan service provision a demographic profile was determined for 500 patients who attended for emergency treatment in the dental faculty over all four seasons. Mean daily rates were Autumn 7.7, Winter 8.8, Spring 7.8 and Summer 3.3. Most patients (45 per cent) arrived by car, 23 per cent came by bus while 19% walked to the dental school. Over three-quarters (77 per cent) came directly from home and the same proportion had endured symptoms for more than 48 hours. Many (60 per cent) had been treated previously at the dental school of whom 31 per cent had received this within the previous month. No less than 85 per cent had no regular dentist. A third of patients had no symptoms, 26 per cent had chronic pain and in 10 per cent the pain was acute in onset. The most frequent treatments were temporary restorations (39 per cent) and pulp extirpation (34 per cent). An irregular daily work load, together with endurance of symptoms by patients, indicates that an emergency service Monday to Friday during normal working hours is adequate.
PK
Keywords: Dental Health Services/utilization; Emergency Medical Services/utilization; Hospitals, University/statistics & numerical data